Neurodevelopmental outcomes of very low birth weight preterm infants during the COVID-19 pandemic - Yen-Chen Lin; Hung-Yang Chang; Chia-Huei Chen; Jui-Hsing Chang; Wai-Tim Jim; Chyong-Hsin Hsu; Chia-Ying Lin; Yu-Xiang Song; Cheng-Wei Chen; Tzu-Yu Liu; Mary Hsin-Ju Ko (Clinical Epidemiology and Global Health)
Background: During the COVID-19 pandemic, parental involvement in NICU and post-discharge follow-up for preterm infants in Taiwan were limited. This study aimed to investigate the impact of the pandemic on the neurodevelopmental outcomes of preterm infants in Taiwan. Method: This was a retrospective study enrolling very-low-birth weight (VLBW) preterm infants born between January 2018 and December 2021 from two hospitals. The pre-COVID-19 group (PCG) consisted of VLBW infants born between January 2018 and April 2019, before the pandemic. VLBW infants born after May 2019 and followed-up for at least 24 months during the pandemic were assigned to the COVID-19 group (CG). The antenatal, perinatal, and postnatal data, and neurodevelopmental outcomes at 12 and/or 24 months corrected age (CA) of the participants were collected and compared. Results: A total of 547 VLBW infants were born during the study period. CG had significantly longer hospital stay and delayed follow-up time compared to PCG. No significant differences were observed in the composite cognitive, language, and motor scores between two groups. The percentages of moderate neurodevelopmental impairment (NDI) were higher at 12 months CA, but not at 24 months. The severe NDI also presented no significant difference between the groups. Conclusion: VLBW preterm infants during the pandemic had extended hospital stays and delayed follow-ups, with higher moderate NDI at 12 months CA. Long-term monitoring and care are essential for this at-risk group.